Springshed protection planning for combating drought in Grobogan District, Central Java - Supangat, A. B. (2022)
Drought occurs almost every dry season in Grobogan District, Central Java. Climate change has resulted in an atypical monthly rainfall distribution, which, along with limestone geology, has made water scarce in some months. One of the efforts to mitigate drought disasters is to revitalize water resources from existing springs. The research aims to develop a spring protection plan through a geological-spatial and participatory approach. The research location is in Kradenan Sub-District, Grogoban District, Central Java Province. The research method starts with identifying springs, delineation of springshed area, formulation of spring and springshed management, and discussion and socialization with stakeholders. The identification results show that the springs are classified as "umbul wadon"type with water discharge ranging from 0.9 to 4.8 l/minute, forming a radial pattern. The area of the springshed is 3,347.7 ha, with more than 70 of the land covered by teak forest plantations. The recommendations for spring conservation activities are organized into three zones: Zones I, II, and III, which differ in range radius, function, and proposed management. In each zone and type of land uses, the potential risk of pollution, prohibited activities, protection strategies and programs, and interested parties as program implementers have been formulated. Several official institutions can aid spring protection management. Together with water users and forest area managers, all institutions agreed to carry out activities to protect and conserve springs and springshed areas. © Published under licence by IOP Publishing Ltd.